THE GAMES OF ORDINARY PASSIONS IN ASCENSIONAL EMOTIONS THE IMAGINARY SOCIAL WORLD OF CLIMBERS (Fiep Bulletin - online, 2015)
The goal of this study is to identify the sensations manifested by the emotions of mountain climbing enthusiasts in their discourses. When a man is on the mountain slopes, he seeks pleasing sensations; however, to obtain these sensations, he breaks the rules of survival, seeking, as near as possible, to walk the line between life and death; getting close to this line is the ecstasy of every mountain adventurer; it is on the threshold of this limit that he is able to interact with his inner self.     With the intent of understanding the subjective world of climbers, ten semi-structured interviews were conducted, seeking, by interpreting the climbers' discourses, useful clues for comprehending the climbing phenomenon, as well as the psychology of these social performers, extracting singularities from each discourse and digging deep into the text to discover meanings in what was and was not said, patent and latent meanings. Free association of ideas, via cue words  Climb, Top, Fear, Pleasure, Frustration, Death, Life, Mountain, Nature and Height  was also used. We based the interpretation of the results on the analysis of the discourse in Eni Orlandi (2001).   The results point to dizziness as the main incentive to climbing, since it precedes the so greatly sought pleasure; we verified that, upon finding themselves in risk situations that threaten their physical integrity, climbers' bodies are invaded by a sensation of vertigo; however, once beyond this moment of anguish, the climber feels himself comfortably out of danger while his body is flooded with a grand, yet rapid, sensation of extreme pleasure.
Keywords: Sport; Climbing; Emotions.